Microplastic ingestion of Indian Mackerel (Rastrelliger kanagurta) sold in an Iloilo City public market. - Layasan, Princess Thrina
Ingestion of microplastics among marine organisms has been reported in several areas worldwide. However, water contamination and consumption of microplastics by fish species in the Philippines is less recognized. The aim of this study was to determine microplastic ingestion, abundance and characteristics of the Indian Mackerel, Rastrellinger kanagurta, being sold in an Iloilo City public market. Microplastic ingestion was determined by visual inspection of the gastrointestinal tracts of 30 individuals followed by potassium hydroxide (KOH) digestion techniques. Microplastic particles were identified based on the absence of cellular or organic structures, having homogeneous thickness across particles, and homogeneous colors and gloss. Microplastics were then categorized according to size, shape, and color. A total of 133 particles were extracted from 93% (n=28) of total fish sampled, translating to a mean abundance of 4.75 ± 0.51 (SE) microplastics per fish. The dominant microplastic shape found was filaments (69%), and the dominant color was blue (43%). The abundance of ingested microplastics was not correlated with total fish length nor total fish weight. The results indicate that Indian mackerel Rastrellinger kanagurta is susceptible to microplastics ingestion. This poses the emerging threat of microplastics in marine organisms consumed by man, e.g. the Indian mackerel and their presence in our seas.